How can a joint European health technology assessment provide an "additional benefit" over the current standard of national assessments? - Elaine Julian; Fabrizio Gianfrate; Oriol de Sola-Morales; Peter Mol; Jean-François Bergmann; Tomas Salmonson; Ansgar Hebborn; Mathilde Grande; Jörg Ruof (Health Economics Review, 2022)
Objectives: We conducted a multi-stakeholder survey to determine key areas where a joint European health technology assessment (HTA) could provide "additional benefit" compared to the status quo of many parallel independent national and subnational assessments. Methods: Leveraging three iterative Delphi cycles, a semiquantitative questionnaire was developed covering evidence challenges and heterogeneity of value drivers within HTAs across Europe with a focus on hematology/ oncology. The questionnaire consisted of five sections: i) background information; ii) value drivers in HTA assessments today; iii) evolving evidence challenges; iv) heterogeneity of value drivers across Europe; v) impact of Europe's Beating Cancer Plan (EBCP). The questionnaire was circulated across n = 189 stakeholder institutions comprising HTA and regulatory bodies, clinical oncology associations, patient representatives, and industry associations. Results: N = 30 responses were received (HTA bodies: 9; regulators: 10; patients' and physicians' associations: 3 each; industry: 5). Overall, 17 countries and EU level institutions were represented in the responses. Consistency across countries and stakeholder groups was high. Most relevant value drivers in HTAs today (scale 1, low to 5, high) were clinical trial design (mean 4.45), right endpoints (mean 4.40), and size of comparative effect (mean 4.33). Small patient numbers (mean 4.28) and innovative study designs (mean 4.1) were considered the most relevant evolving evidence challenges. Heterogeneity between regulatory and HTA evidence requirements and heterogeneity of the various national treatment standards and national HTA evidence requirements was high. All clinical and patient participants stated to have been with EBCP initiatives. Conclusions: For a European HTA to provide an "additional benefit" over the multitude of existing national assessments key methodological and process challenges need to be addressed. These include approaches to address uncertainty in clinical development; comparator choice; consistency in approaching patient-relevant endpoints; and a transparent and consistent management of both HTA and regulatory procedures as well as their interface, including all involved stakeholder groups.
Keywords: 330; Access; Clinical trial design; Comparators; Endpoints; EU HTA; Europe's Beating Cancer Plan; Patient-relevance; Real world evidence